High prevalence of hepatic steatosis and hepatic fibrosis in patients with type 2 diabetes mellitus. (December 2021) - Gupta, Aanchal; Anoop, Shajith; Ansari, Irshad Ahmad; Prakash, Satya; Misra, Anoop
Summary: Aim: To determine the prevalence of hepatic steatosis and fibrosis in patients with T2DM from North India. Research design and methods: In this cross-sectional study, Asian Indian patients with T2DM (n, 250) underwent liver ultrasonography (USG), Fibroscan for assessment of hepatic steatosis (Controlled Attenuation Parameter, CAP) and hepatic fibrosis (Kilopascals, kPa) respectively. Pearson's correlation analysis & logistic regression analysis for significant predictors of hepatic steatosis and fibrosis were done. The cut-off value of liver span was calculated by ROC-AUC analysis. Results: Grade 3 hepatic steatosis was seen in 213 T2DM patients (85.2%). It was higher in males than females and in those with high BMI values. Any degree of fibrosis and severe fibrosis were seen in 205 (62%) and 46 (18.4%) patients, respectively; these were higher in males, specifically in those with BMI >30 kg/m 2, and diabetes of a duration more than 5 years. BMI and SGPT were the significant predictors of hepatic steatosis. An increase of 1 unit of BMI above 23 kg/m 2 led to 19.6 times increased risk of hepatic steatosis in T2DM patients aged 50 years and above. SGOT and GGTP were significant predictors of any degree of hepatic fibrosis. On ROC-AUC analysis, liver span cut-off values of ≥16.4 cms and ≥16.8 cm in males and females respectively, were predictive of hepatic fibrosis. Conclusion: High prevalence of grade 3 hepatic steatosis and hepatic fibrosis needs increased vigilance and corrective lifestyle and pharmacological measures. Asian Indian patients with T2DM and BMI >30 kg/m 2, with duration of diabetes above 5 years & an ultrasound derived liver span ≥16.4 cms, should be further evaluated for hepatic fibrosis. Highlights: High prevalence of hepatic steatosis and fibrosis in Asian Indians with T2DM. Mild & moderate hepatic fibrosis prevalent in 62% (n, 205/250) of patients with T2DM. Hepatic fibrosis - highly prevalent – obese (BMI 30 kg/m 2 ) patients with T2DM > 5 yrs Liver size > 16.4 cms (in males) & 16.8 cms (in females) predict hepatic steatosis.